2020
DOI: 10.21494/iste.op.2020.0513
|View full text |Cite
|
Sign up to set email alerts
|

L’éducation, la formation et l’économie de la connaissance en Algérie : Quelques éléments d’évaluation empiriques

Abstract: Ce papier examine la situation de l'éducation et de la formation au regard de leur contribution potentielle à l'entrée de l'économie algérienne dans l'économie de la connaissance. Après avoir rappelé les liens entre éducation, formation et accumulation de capital humain et le rôle de ce dernier dans la croissance, une présentation à la fois quantitative et qualitative (évaluation empirique) du système de formation est proposée permettant d'en faire ressortir les points forts et les faiblesses. Les résultats ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Despite the rather encouraging indicators of research activities within the academic sphere in Algeria, all research studies in this area have found that vertical collaborations, ie the flow of information and knowledge between the world of research and the actors of the innovation system remain weak (Haudeville and Younes Bouacida, 2020;Younes Bouacida, 2018;Ben Slimane and Ramadan, 2017;Amdaoud, 2016;Djeflat, 2009). Indeed, the global ranking of the Global Index of Innovation 2018 highlights the weakness of vertical collaborations and the lack of the impact of knowledge in Algeria since it is positioned for these two indicators at the bottom of the table (at the 111th and 101st respectively).…”
Section: Vertical Collaborationsmentioning
confidence: 99%
“…Despite the rather encouraging indicators of research activities within the academic sphere in Algeria, all research studies in this area have found that vertical collaborations, ie the flow of information and knowledge between the world of research and the actors of the innovation system remain weak (Haudeville and Younes Bouacida, 2020;Younes Bouacida, 2018;Ben Slimane and Ramadan, 2017;Amdaoud, 2016;Djeflat, 2009). Indeed, the global ranking of the Global Index of Innovation 2018 highlights the weakness of vertical collaborations and the lack of the impact of knowledge in Algeria since it is positioned for these two indicators at the bottom of the table (at the 111th and 101st respectively).…”
Section: Vertical Collaborationsmentioning
confidence: 99%